Cobalt Phthalocyanine Cross‐Linked Polypyrrole for Efficient Electroreduction of Low Concentration CO2 To CO. Issue 23 (4th November 2022) - Chen, Jin‐Mei; Xie, Wen‐Jun; Yang, Zhi‐Wen; He, Liang‐Nian
Abstract: Immobilizing cobalt phthalocyanine (CoPc) onto the electrode surface is a significant approach to performing efficient electrochemical CO2 reduction reaction (ECO2 RR). Herein, sulfylphenoxy decorated CoPc cross‐linked polypyrrole is prepared by in situ polymerization on the surface of carbon cloth. The synthesized N‐rich catalyst exhibits above 95 % Faradaic efficiency toward CO (FECO ) at −0.9 V versus reversible hydrogen electrode (RHE) at least for 10 h in aqueous solution and even enables direct electrolysis at low CO2 concentrations, being potential for coupling ECO2 RR with CO2 capture. This facile in situ polymerization strategy would pave the way for developing efficient and practical electrocatalysis for ECO2 RR. Abstract : Link together : Sulfylphenoxy decorated cobalt phthalocyanine cross‐linked polypyrroles prepared by in situ polymerization on the surface of carbon cloth performed well for directly electrocatalytic CO2 reduction at low CO2 concentrations, showing potential for coupling electrochemical CO2 reduction reaction (ECO2 RR) with CO2 capture.